Likovna edukacija in okoljska trajnost - Duh, Matjaž; Herzog, Jerneja; Zupančič, Tomaž (University of Maribor Press, 2016)
Art Education and Environmental Sustainability. The monograph is one of the first attempts in Slovenia at a comprehensive scientific discussion of the relation between the care for preserving human being’s natural environment and art education. The theoretical section aims to juxtapose and examine the relations between environmental sustainability, on the one hand, and visual art, general education and art education, on the other. The empirical surveys cover preschool and school-age children, preschool teachers and university students. The studies showcase the implementation of artistic activities during the preschool period, in primary schools and in secondary school practices. We established that the environmental sustainability of today shows multifaceted connections with contemporary art and education. Ecological content forms an important part of the content in kindergartens and schools. The content of art education study programmes at universities should include more topics connected with sustainable development, which would increase students’ interest in and awareness of the importance of this current problem.